Effect of field utilization factor on air breakdown level under impulse lightning in point-sphere electrode system - Abdullah @ Abdul Rahman, Suhaimi (2014)
Nowadays, the high voltage power is very important to industries. Due to growing of technology, the power equipment also improves and innovates to have the best performance. The high voltage power equipment is mainly subjected to spark over voltage. Spark over can be useful in some cases and may give bad effect or damage the machine. Therefore the research on the behavior of spark over, breakdown voltage is signified in the electrical engineering designing process. The project is started with an experimental setup to get the standard impulse voltage. This lightning impulse voltage is ensuring to follow the standard of BS EN 60060-1:2010. The procedure of this experiment follows the TERCO catalogue documentation. In this project, the standard point-sphere gap is use to measurements of U50 breakdown voltages. A metallic point electrode is separated by a certain distance form a sphere gap. Also, the gap length between the spheres will be varied from 1 cm to 3 cm. The procedure to get U50 is followed to Up and Down method. FEMM software is use for simulation and analysis of electric field distribution for point-sphere electrode. This software provides a wide range of simulation applications for controlling the complexity of both modelling and analysis of a system. The value of U50 obtained is used in this simulation. The characteristic of field intensity will be analysed for all gaps. The average of field intensity and field utilization factor F.U.F will be analysed by using this software